Systemy aberrometryczne w laserowej chirurgii refrakcyjnej - Wyględowska-Promieńska, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The wavefront sensing device provides a new and objective way of mapping the profile of refraction and of higher order defocus. Higher-order optical errors of the human eye are often responsible for reduced visual acuity, in spite of an optimal spherical or cylindrical refraction. These optical aberrations are of natural origin or can results from operations on the eye, involving optical structures. Nowadays, there are four different methods of wavefront technology available: Concept of „Outgoing” Reflective Aberrometry, Concept of „Retinal Imaging” Aberrometry, Concept of „Ingoing” Adjustable Aberrometry (Spatially Resolved Refractometer), Concept of „Double Pass” Aberrometry. Wavefront analysis is a more sophisticated method of defining aberrations that the surgeon is trying to correct through refractive surgery.